The Potential of Sawarna Beach as an Educational-Ecotourism Area and Its Utilisation in Biology Education: A Systematic Review - Rifqiawati, Ika; Aisya, Putri Nurul (Universitas Sultan Ageng Tirtayasa, 2025)
Tourism is very important for the economy because of its natural beauty and cultural diversity, so this sector must be developed. Tourism is one of the most profitable branches of the economy and has great potential to become a growing asset that can increase national income. One example is Sawarna Beach, located in Sawarna Village, Bayah District, Lebak Regency, Banten Province, which has excellent potential for development, especially in terms of eco-tourism. This study aims to delve deeper into information related to the potential of Sawarna Beach from various aspects regarding how Sawarna Beach can become an Edu-Eco-Tourism location and its utilisation in biology education. This study employs a qualitative approach using a systematic review to synthesise (summarise) the results of qualitative descriptive research. The findings of this literature review indicate that Sawarna Beach possesses diverse tourism potential and is suitable for development as an Edu-Ecotourism site prioritising ecotourism principles, particularly in educating and empowering local communities. The natural potential of Sawarna Beach can be developed through biology learning themes such as Biodiversity, Ecosystem Interactions and Their Roles, and Environmental Change and Conservation. Educational products that can be developed from the natural potential include books, locally-based teaching modules, worksheets, observation guides, posters, and others